Palestine and Israel, Still a Challenge to Justice - Grandi, Barbara (Archives of Business Research, 2024)
According to ONU Resolution n. 181, approved on 1947 November the 29th, providing the establishment of two States, one for the Israeli people – who declared their independence on 1948 the 14th of May, and one for the Arab-Palestininas, having never established themeselves into the form of a distinguished State, Israel, as a sea land standing in the Middle Est region between the Mediteranean sea and Asia, is nowadays and since 1948 formally a State2 . It is opposed to be as such by some Palestinian organizations and authorities, intermittentely supported by foreign countries: Palestininas contest to Israel its legal establishment into such an independent nation, which is considered to be remedial to the persecution the Jewish people faced worldwide for their religious belief, and by followers of nazist ideologies particularly.